COVID-19 vaccine acceptance among cold-chain workers in Shenzhen, China: A cross-sectional survey. Issue 5 (30th November 2022) - Liu, Lizhen; Zhang, Minyi; Chen, Hongbiao; Xian, Juxian; Cao, He; Zhou, Xiaofeng; Gu, Zihao; Liu, Huamin; Li, Qiushuang; Wu, Fei; Chen, Qing; Lin, Qihui
ABSTRACT: Given the high level of exposure to SARS-CoV-2, cold-chain workers are considered priority vaccination groups. To date, many studies have reported on the willingness within distinct populations to be vaccinated against COVID-19, whereas it has not been reported among cold-chain workers worldwide. To address this void, we conducted a cross-sectional survey to gather general information, COVID-19-related knowledge, attitudes, and practices (KAP), and willingness to receive a COVID-19 vaccine among cold-chain workers in Shenzhen, China. Binary logistic analyses were conducted to explore the associations between COVID-19-related KAP factors and the willingness for COVID-19 vaccination. Among 244 cold-chain workers, 76% indicated that they were willing to be vaccinated. Knowledge about SARS-CoV-2, comprehending the most effective prevention, understanding the transmission routes, and recognizing the priority vaccination groups were positively associated with willingness to be vaccinated against COVID-19. Regarding attitude factors, perceiving the social harmfulness and severity of COVID-19 were related to a higher willingness to vaccination. Participants considering themselves a priority group for COVID-19 vaccination were more likely to get vaccinated. For practice factors, attaining more knowledge and higher self-reported compliance with maintaining adequate ventilation were also positively associated with the dependent variable. Agreement on the importance of COVID-19 vaccination was the most frequent reason for accepting the COVID-19 vaccine; additionally, concerns about side effects and insufficient understanding of efficacy were the main factors contributing to vaccine refusal. Enhancing KAP levels related to COVID-19 helps promote vaccine acceptance. Health authorities should promptly implement educational activities following the updated vaccine status among cold-chain workers.